hipertensi, perilaku, makan, lan PERILAKU MAKAN DENGAN KEJADIAN HIPERTENSI PADA LANSIA DI DESA GAYAMAN MOJOANYAR MOJOKERTO - Eka Diah Kartiningrum (Jurnal Keperawatan Malang, 2018)
Abstract Hypertension in the elderly is a disease characterized by an increase in blood pressure continuously. Hypertension is caused by many factors such as eating behavior. The purpose of this study was to analyze the effect of eating behavior to the incidence of hypertension in the elderly. This study used crossectional design with elderly group as population, as many as 33 orsng was taken as sample. The data of eating behavior was collected by using interview technique while hypertension incidence was determined based on observation of blood pressure by using tensimeter. The results then analyzed by using logistic regression test. The results showed that as many as 54.5% of respondents have bad eating behavior, while 60.6% of respondents expressed hypertension. Logistic regression results show that eating behavior greatly affects the incidence of hypertension. Elderly people who have bad eating behavior have a risk of hypertension 5.25 times greater than the elderly with good eating behavior. Eating behavior determines the intake of nutrients absorbed in the human body. Foods that contain high salt, high fat and low fiber cause stability disorders sodium and potassium levels in the body so that the impact on the increase in blood pressure. Therefore, the family should make the setting of eating behavior ranging from the arrangement of the menu, the frequency and amount of food consumption family level so that all family members can pass through the elderly with both. Keyword:hypertension, habit, eating, elderly